Multilevel marketing (MLM) vs pyramid scheme - from legal perspective - A. Rahman, Aspalella; Nik Mat, Nik Kamariah (2001)
Multilevel marketing is a popular marketing method often practiced by direct selling companies.However, it has been manipulated in the form of the illegal pyramid scheme or commonly known as the get-rich-quick scheme, This paper intends to discuss the differences between MLM and pyramid schemes, the regulations on MLM and anti-pyramid laws in other countries, and the loopholes of the existing Direct Sales Act 1993 in Malaysia especially regarding provisions on MLM technical operations.It was suggested that amendments or provisions should be made on the MLM operations particularly provisions concerning start-up fees, inventory loading and a balanced compensation system.Additionally, consumer education and awareness as well as stringent enforcement should also be enforced.